Mechanical, thermal, and barrier properties of starch films incorporated with chitosan nanoparticles - Ahmad Shapi’i, Ruzanna; Othman, Siti Hajar; Kadir Basha, Roseliza; Naim, Mohd Nazli (Walter de Gruyter GmbH, 2022)
The mechanical, thermal, and barrier properties of tapioca starch films produced using a solvent casting method with varying concentrations of chitosan nanoparticles (CNPs; 5, 10, 15, 20, 25, 30, 35% w/w of solid starch) were investigated. The addition of 15% w/w CNP (size range: 20–50 nm) to the starch films (starch/CNP films) enhanced the tensile strength from 1.12 to 10.03 MPa (7.96-fold increment) and elongation at break from 67.00 to 90.77% (0.35-fold increment). However, the thermal stability of the starch films reduced slightly whereby the maximum degradation temperature decreased from 316.32 to 289.11°C (0.09-fold decrement) with the addition of CNP. The opacity of 15% w/w starch/CNP films increased from 8.07 to 14.67 due to the presence of CNP within the starch matrix that hinders the light transmission pass through the film. Furthermore, reductions in the water vapor permeability from 1.1 × 10−11 to 0.63 × 10−11 g/Pa h m (4-fold increment) and oxygen permeability from 7.38 × 10−3 to 3.59 × 10−3 cm3/m day Pa (0.51-fold increment) of the films were observed. Starch/CNP films fabricated in this work exhibit enhanced the mechanical and barrier properties, thus proving the promising potential to be employed as food packaging materials.